2013
DOI: 10.1603/me12264
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Natural Vertical Transmission of West Nile Virus by California <I>Culex</I> (Diptera: Culicidae) Mosquitoes

Abstract: Culex (Diptera: Culicidae) mosquitoes, the primary summer vectors of West Nile virus (family Flaviviridae, genus Flavivirus, WNV), also may serve as overwintering reservoir hosts. Detection of WN viral RNA from larvae hatched from eggs deposited by infected females during late summer and fall may provide evidence for the vertical passage of WNV to overwintering cohorts. To determine whether vertical transmission to the overwintering generation occurs in populations of Culex mosquitoes throughout California, la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 41 publications
1
39
1
1
Order By: Relevance
“…Although WNV was not detected in adult progeny of colonized f. pipiens females, another colonized strain of f. pipiens from the Sacramento Valley, CA, successfully transmitted WNV to larval and adult progeny in a previous study. 68 In this study, f. molestus females were uniparous (after autogenous oviposition) before imbibing an infective bloodmeal, perhaps allowing increased dissemination of WNV to the reproductive tract, as vertical transmission rates have been shown to increase with the number of gonotrophic cycles completed by infected females. 67 The frequency of vertical transmission also may be influenced by rearing temperature and mosquito species and strains.…”
Section: Wolbachiamentioning
confidence: 83%
See 1 more Smart Citation
“…Although WNV was not detected in adult progeny of colonized f. pipiens females, another colonized strain of f. pipiens from the Sacramento Valley, CA, successfully transmitted WNV to larval and adult progeny in a previous study. 68 In this study, f. molestus females were uniparous (after autogenous oviposition) before imbibing an infective bloodmeal, perhaps allowing increased dissemination of WNV to the reproductive tract, as vertical transmission rates have been shown to increase with the number of gonotrophic cycles completed by infected females. 67 The frequency of vertical transmission also may be influenced by rearing temperature and mosquito species and strains.…”
Section: Wolbachiamentioning
confidence: 83%
“…pipiens complex populations in California appear to be competent vectors for WNV, the principal question is whether WNV can persist in these populations during winter. Both f. molestus and f. pipiens 68 from California are capable of vertically passing virus to their offspring during late summer. Because the majority of Cx.…”
Section: Spielmanmentioning
confidence: 99%
“…Assuming virus is passed to the egg, it must then pass transstadially from egg to larvae, to pupae and to adult, disseminating to the salivary glands or ovaries for onward HT or VT. Hardy et al [110] proposed that virus is inactivated during metamorphosis, which was supported by a reduction in viral titres transstadially during development [111]. In contrast, LACV transmission to progeny of orally infected Aedes triseriatus indicated that viral load was higher in larvae compared to eggs [106] and similarly increased in each stage from egg to adult with most larval and adult tissues supporting replication [112].…”
Section: Time Of Samplingmentioning
confidence: 99%
“…Thus, for these mosquitoes to become infected with WNV they require infection by VT, not oral infection, prior to overwintering. VT of WNV by Culex mosquitoes and subsequent detection in overwintering populations has been recorded [111,128]. Therefore, when considering RVFV in temperate regions outside Africa, it may be necessary to consider a similar overwintering model.…”
Section: Temperaturementioning
confidence: 99%
“…1 Vertical transmission of arboviruses occurs from an adult female mosquito to its eggs and progeny. This may be an important source of maintenance for arboviruses such as dengue virus [3][4][5] and West Nile virus, 6,7 particularly during unfavorable environmental conditions. Inconsistent findings are reported for the existence of vertical transmission of CHIKV; if it does occur, it is infrequent.…”
Section: Introductionmentioning
confidence: 99%